TRADE LIBERALISATION AND NIGERIA’S ECONOMIC DEVELOPMENT (2015-2020): AN APPRAISAL - Patrick, Desmond (African Journal of Social and Behavioural Sciences, 2025)
This study examines the impact of trade liberalisation on Nigeria’s economic development from 2015 to 2020. It elucidates the extent to which increased competition, resulting from trade openness, has impacted Nigeria’s economic development and examines how institutional weaknesses have hindered Nigeria’s economic development in recent times. The study adopted the comparative advantage theory as its major theoretical framework of analysis and the liberal theory as it supporting theory. It benefited from a qualitative research design, which helped to gather insights from policymakers, business leaders, and experts on the impact of trade liberalisation on Nigeria’s economic development. Data were collected through secondary methods, i.e., from published books, existing literature, articles, journals, newspaper reports, documentaries, and research works, in relation to the “case study”. The collected data were analysed using thematic analysis. Based on the presentation and analysis of the study, it was revealed that increased competition has both positive and negative impacts on Nigeria’s economic development. While competition can drive innovation and productivity, it can also lead to market dominance by foreign firms, job losses, and reduced domestic production. Institutional weaknesses, such as corruption and inadequate regulatory frameworks, can hinder economic development in Nigeria. The study recommended that the Nigerian government should prioritise institutional reforms to address corruption, improve regulatory frameworks, and enhance the business environment. This could include establishing specialised courts for commercial disputes, improving transparency in public procurement, and enhancing the regulatory agencies’ capacity.